(untitled) (Indian Journal of Animal Production and Management, 2024)
A study was carried out to know the relationship between variation in mammary system conformation traits and milk yield in Jaffarabadi buffaloes. 150 buffaloes selected from dairy farms located in and around Hyderabad were utilized for the study. Among udder shapes, bowl shaped udder was most common followed by globular, pendulous and goaty udder with 53.3%, 26.66%, 16% and 4%, respectively and cylindrical shaped teats was most common followed by conical, funnel, pear and bottle shapes with 48.0%, 22.66%, 13.33%, 10% and 6%, respectively. The average udder length, width and depth in buffaloes ranged from 62.64 ± 0.74 (globular udder) to 67.81 ± 1.03 cm (pendulous udder), 50.51 ± 0.35 (bowl udder) to 54.07 ± 1.35 cm (goaty udder) and 17.26 ± 0.27 cm (bowl udder) to 20.25 ± 0.74 cm (goaty udder), respectively. Positive and highly significant (P<0.01) phenotypic correlation observed among three udder biometrics, indicating their close inter-relation. The mean teat lengths recorded for left fore, right fore, left hind and right hind teats were 7.69 ± 0.10 cm, 7.79 ± 0.11cm, 8.63 ± 0.16 cm and 8.67 ± 0.16 cm, respectively. The mean teat diameter ranged from 3.09 ± 0.06 cm (globular udder) to 3.57 ± 0.31 cm (goaty udder). Teat diameter was highest in goaty udder followed by pendulous, bowl and globular shaped udders. The mean milk yield/day in Jaffarabadi buffaloes with different udder shapes recorded was 8.48 ± 0.11, 8.12 ± 0.16, 7.97 ± 0.14 and 7.82 ± 0.13 Kg in bowl, globular, pendulous and goaty udders, respectively. The mean milk yield/day in various teat shapes recorded were 8.61 ± 0.12, 8.33 ± 0.27, 8.23 ± 0.15, 8.08 ± 0.18 and 7.67 ± 0.13 Kg in cylindrical, bottle, funnel, pear and conical shaped teats, respectively. Positive and highly significant (P<0.01) correlation observed between mammary system conformation traits and milk yield. The study concludes that, Jaffarabadi buffaloes with bowl shaped udder and cylindrical shaped teats were found to give more milk, Hence, these udder conformation traits may be helpful in their selection for higher milk yields.